2021
DOI: 10.1088/1748-605x/abf88d
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous zirconia surfaces with anti-biofilm properties for dental implants

Abstract: Cytocompatible bioactive surface treatments conferring antibacterial properties to osseointegrated dental implants are highly requested to prevent bacteria-related peri-implantitis. Here we focus on a newly designed family of mesoporous coatings based on zirconia (ZrO2) microstructure doped with gallium (Ga), exploiting its antibacterial and pro-osseo-integrative properties. The ZrO2 films were obtained via sol–gel synthesis route using Pluronic F127 as templating agent, while Ga doping was gained by introduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Likewise, Agostino et al [ 131 ] took advantage of the antibacterial and osseointegration properties of Ga and fabricated mesoporous zirconia (ZrO 2 ) materials with Ga coating. The results showed that the existence of Ga 3+ dramatically reduced the metabolism of oral symbiotic Streptococcus salivarius and Aggregatibacter actinomycetemcomitans ( P. gingivalis and A. actinomycetemcomitans ) along with confirming the protective effect of Ga coating on cells against bacterial infestation The protective effect of Ga coating on cells against bacterial infection was also confirmed.…”
Section: Antibacterial Application Of Lm-based Materialsmentioning
confidence: 99%
“…Likewise, Agostino et al [ 131 ] took advantage of the antibacterial and osseointegration properties of Ga and fabricated mesoporous zirconia (ZrO 2 ) materials with Ga coating. The results showed that the existence of Ga 3+ dramatically reduced the metabolism of oral symbiotic Streptococcus salivarius and Aggregatibacter actinomycetemcomitans ( P. gingivalis and A. actinomycetemcomitans ) along with confirming the protective effect of Ga coating on cells against bacterial infestation The protective effect of Ga coating on cells against bacterial infection was also confirmed.…”
Section: Antibacterial Application Of Lm-based Materialsmentioning
confidence: 99%
“…Hypoallergenic implants offer several benefits over traditional implants beyond decreased immunogenicity. The design objective is to reduce infection risk because hypoallergenic implants are made from materials that resist bacterial growth [34][35][36] . Furthermore, they may reduce prosthetic-related complications because they can be absorbed fully by the body.…”
Section: Implant Manufacturing Engineer Perspectivementioning
confidence: 99%
“…Silver nitrate is a common source of silver ions, whose impact on bacteria and human cells is well known [55,56]. Recently, the ability of gallium nitrate to prevent the formation of biofilm and to eradicate was already assessed [23,24]. On the basis of previous studies [57,58], MIC (minimal inhibitory concentration) of silver and gallium has been considered to prepare effective antibacterial coatings.…”
Section: Discussionmentioning
confidence: 99%
“…A possible method to provide CoCrMo alloys with antimicrobial properties is to develop coatings integrating cations with well-known antibacterial behaviour [16,17], such as silver (Ag) [18,19], copper (Cu) [20], zinc [20,21] and gallium (Ga) [22][23][24]. Among them, Ag has aroused lively interest in the biomedical field as well as some applications have reached the maturity for clinical use [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation